Knowledge-Based Software Engineering : Proceedings of the Seventh Joint Conference on Knowledge-Based Software Engineering - Tõugu, Enn, 1935-; Yamaguchi, Takahira (Frontiers in artificial intelligence and applications, 2006)
This publication addresses the research in theoretical foundations, practical techniques, software tools, applications and / or practical experiences in knowledge-based software engineering. The book also includes a new field: research in web services and semantic web. This is a rapidly developing research area promising to give excellent practical outcome, and interesting for theoretically minded as well as for practically minded people. The largest part of the papers belongs to a traditional area of applications of artificial intelligence methods to various software engineering problems.